2008
DOI: 10.1038/ejhg.2008.130
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic analysis reveals a euchromatic configuration in the FMR1 unmethylated full mutations

Abstract: Fragile X syndrome (FXS) is caused by the expansion of a CGG repeat in the 5 0 UTR of the FMR1 gene and the subsequent methylation of all CpG sites in the promoter region. We recently identified, in unrelated FXS families, two rare males with an unmethylated full mutation, that is, with an expanded CGG repeat (4200 triplets) lacking the typical CpG methylation in the FMR1 promoter. These individuals are not mentally retarded and do not appear to be mosaic for premutation or methylated full mutation alleles. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 50 publications
4
89
0
1
Order By: Relevance
“…These epigenetic changes, induced by 5-azadC, appeared to restore a euchromatic configuration of the FMR1 promoter in treated FXS cells (see Fig. 2), effectively transforming a methylated full mutation into an unmethylated full mutation (UFM) Tabolacci et al, 2008a]. 5-azadC effects increased with dose and treatment time [Chiurazzi et al, 1999;Pietrobono et al, 2002], but 4 weeks after treatment was discontinued we observed regain of DNA methylation in the FMR1 promoter and loss of transcription [Pietrobono et al, 2002].…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 72%
See 2 more Smart Citations
“…These epigenetic changes, induced by 5-azadC, appeared to restore a euchromatic configuration of the FMR1 promoter in treated FXS cells (see Fig. 2), effectively transforming a methylated full mutation into an unmethylated full mutation (UFM) Tabolacci et al, 2008a]. 5-azadC effects increased with dose and treatment time [Chiurazzi et al, 1999;Pietrobono et al, 2002], but 4 weeks after treatment was discontinued we observed regain of DNA methylation in the FMR1 promoter and loss of transcription [Pietrobono et al, 2002].…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 72%
“…Kumari and Usdin [2010] also reported increased methylation of lysine 20 on histone 4 (H4K20) near the CGG expansion. All these epigenetic changes result in heterochromatinization of the FMR1 locus [Coffee et al, 2002;Tabolacci et al, 2005Tabolacci et al, , 2008a, preventing transcription and resulting in absence of the FMRP protein. An exhaustive overview of FMRP functions is provided by Bagni and Oostra [2013] in this same issue.…”
Section: Fragile X Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…In 1991 Verkerk et al identify the FMR1 gene locus Xq27.3, corresponding to the fragile site sensitive to folate deficiency (FRAXA). Its mutation is described as the cause of fragile X syndrome and it is characterized by the presence of a CGG trinucleotide repeat in the in the promoter region of the FMR1 gene (14,15,16 (17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of FMR1 transcription are slightly increased compared with controls, but translational efficiency of the corresponding mRNA is reduced. 6,7 These studies demonstrated that CGG expansion in the range of FM per se does not prevent FMR1 transcription, DNA methylation being …”
mentioning
confidence: 99%